2008
DOI: 10.1002/gcc.20619
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution genomic profiling of adenomas and carcinomas of the salivary glands reveals amplification, rearrangement, and fusion of HMGA2

Abstract: Carcinoma ex pleomorphic adenoma (Ca-ex-PA) is an epithelial malignancy developing within a benign salivary gland pleomorphic adenoma (PA). Here we have used genome-wide, high-resolution array-CGH, and fluorescence in situ hybridization to identify genes amplified in double min chromosomes and homogeneously staining regions in PA and Ca-ex-PA and to identify additional genomic imbalances characteristic of these tumor types. Ten of the 16 tumors analyzed showed amplification/gain of a 30-kb minimal common regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
124
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(139 citation statements)
references
References 41 publications
5
124
2
Order By: Relevance
“…4 Mb segment in 8q12.1, containing the PLAG1 gene, is of importance for malignant transformation of benign salivary pleomorphic adenomas. 43,44 In summary, we have shown that low-grade mucoepidermoid carcinomas have normal or nearnormal genomic profiles, express the CRTC1-MAML2 fusion, and have a favorable clinical outcome. In contrast, the majority of high-grade tumors had multiple genomic imbalances, were negative for the CRTC1-MAML2 fusion, and developed frequent metastasis and/or recurrences.…”
Section: Discussionmentioning
confidence: 91%
“…4 Mb segment in 8q12.1, containing the PLAG1 gene, is of importance for malignant transformation of benign salivary pleomorphic adenomas. 43,44 In summary, we have shown that low-grade mucoepidermoid carcinomas have normal or nearnormal genomic profiles, express the CRTC1-MAML2 fusion, and have a favorable clinical outcome. In contrast, the majority of high-grade tumors had multiple genomic imbalances, were negative for the CRTC1-MAML2 fusion, and developed frequent metastasis and/or recurrences.…”
Section: Discussionmentioning
confidence: 91%
“…There are a handful of salivary gland tumors that have been demonstrated to have recurring cytogenetic abnormalities including adenoid cystic carcinomas [t(6;9) (MYB-NFIB)] [8][9][10], mucoepidermoid carcinomas [t(11:19) (MECT1-MAML2)] [11,12], pleomorphic adenomas (PLAG1 and HMGA2 rearrangements) [13][14][15][16][17], and hyalinizing clear cell carcinoma [t(12;22) (EWSR1-ATF)] [18,19]. In the majority of these tumors, the morphology is distinctive enough to allow for a diagnosis and molecular confirmation is typically not necessary.…”
Section: Introductionmentioning
confidence: 99%
“…HMGA2 is ascribed an important role in the control of stem-cell development and proliferation, and also high levels of HMGA2 is found in many benign, as well as malignant, tumours [33,34]. HMG proteins are the most abundant non-histone DNAbinding chromatin factors in the eukaryotic nucleus involved in up-and downregulation of several genes [33].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, epithelial-mesenchymal transition (EMT) has been suggested as a novel pathway playing a key role in the pathogenesis of tubulointerstitial fibrosis in DN and blockage of EMT has been shown to delay progression to DN [33,34]. Of note, transcriptomic analyses of TGF-β-stimulated EMT in NAMRU mouse mammary gland (NMuMG) cells identified HMGA2 as a main target involved in the control of epithelial differentiation [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation